Financial cycles under diagnostic beliefs - Antoine Camous; Alejandro Van der Ghote (European Central Bank (ECB), 2022)
Swift changes in investors' sentiment, such as the one triggered by COVID-19 global outbreak in March 2020, lead to financial tensions and asset price volatility. We study the interactions of behavioral and financial frictions in an environment with endoge- nous risk-taking and capital accumulation. Agents form diagnostic expectations about future stochastic outcomes: recent realizations of aggregate shocks are expected to persist. This behavioral friction gives rise to sentiment cycles with excessive invest- ment and occasional safety traps. The interactions with financial frictions lead to an endogenous amplification of financial instability. We discuss implications for policy interventions.
Keywords: E32; E44; E71; 330; Financial Cycles; Diagnostic Beliefs; Macro-prudential Policy